Navigating the Maritime: Technology for the Defense of the Indonesian National Capital City (IKN) in the Makassar Strait - Azizan, Akmal; Zahra, Salma; Sophia, Sally (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
Maritime defense, particularly in critical waterways like the Makassar Strait, is paramount due to its geopolitical significance. This study aims to evaluate the efficacy of virtual maritime technology alongside traditional maritime defense methods. This study seeks to assess virtual maritime technology's efficacy, evaluate existing knowledge gaps regarding maritime defense in Southeast Asia, and propose practical policy measures for enhancing defense in the Makassar Strait region. By employing a comprehensive research design, this study analyzes the strategic importance of the Makassar Strait, the strengths and weaknesses of traditional defensive measures, and potential applications of virtual maritime technology through case studies and comparative analysis. The findings reveal novel insights into utilizing virtual maritime technology as a force multiplier, particularly in the context of the Makassar Strait. Additionally, the study identifies overlooked aspects such as cooperative defense, moral concerns, and the under-researched nature of virtual maritime in Southeast Asia. In conclusion, this study underscores the significance of integrating virtual maritime technology within the comprehensive defense framework to bolster maritime defense. It emphasizes the need for collaborative approaches and offers practical policy proposals for effectively deploying these technologies. The research contributes to bridging knowledge gaps in maritime defense and provides actionable insights for policymakers and military professionals. Advocating for virtual maritime technology offers a promising strategy for safeguarding Indonesia's capital city (IKN) and securing vital maritime routes like the Makassar Strait.